Evaluasi data curah hujan terukur dan satelit PERSIANN-CCS dalam analisis debit banjir rancangan terhadap debit banjir terukur di DAS Tukad Petanu - I Gusti Ngurah Kade Mahesa Adi Wardana; I Gusti Lanang Made Parwita; I Nyoman Anom Purwa Winaya (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2024)
Analysis of design flood discharge is required in waterworks planning, especially to determine the amount of design flood discharge in a watershed. The unit hydrograph method is a commonly used method in the calculation of design flood discharge, where this method requires rainfall data in its analysis. Current technology makes it possible to use satellite data as an alternative to data from rain gauge stations whose distribution is very limited. This research aims to obtain the level of suitability of the utilisation of satellite and measured rainfall data which will be used as a solution in predicting the design flood discharge. The rainfall data used in this study uses measured rainfall data from rain gauge stations and PERSIANN-CCS satellite rainfall data. The calculation results from both data will then be validated with the river flood discharge recorded at the Tukad Petanu Hulu Automatic Water Level Recorder (AWLR) Station and seen the level of conformity. This research shows that the design flood discharge in the Tukad Petanu watershed analysed using the Nakayasu Synthetic Unit Hydrograph based on measured rainfall data for 5, 10, 25, 50, and 100-year return periods is 58.16 m3/sec, 67.99 m3/sec, 82.76 m3/sec, 95.88 m3/sec, and 110.81 m3/sec, while based on PERSIANN-CCS satellite rainfall data for the same return period of 93.00 m3/sec, 101.12 m3/sec, 109.42 m3/sec, 113.98 m3/sec, and 117.65 m3/sec, respectively. The design flood discharge in the Tukad Petanu watershed based on measured discharge data at the Tukad Petanu Hulu AWLR Station is 15.75 m3/sec, 24.94 m3/sec, 42.47 m3/sec, 61.28 m3/sec, and 86.63 m3/sec for the same return period, respectively. The design flood discharge in the Tukad Petanu watershed analysed with the Nakayasu Synthetic Unit Hydrograph Method based on measured rainfall data has a better level of fit than the PERSIANN-CCS satellite rainfall data, where measured rainfall data provides lower VE, RE, and RMSE values when compared to PERSIANN-CCS satellite rainfall data.